Analysis of Conceptual Understanding Improvement Through Solar Cell Experiments in Scientific-Based Physics Learning - Boisandi Boisandi; Anita Anita; Aulia Aulia; Fila Delfia (Universitas PGRI Pontianak, 2023)
The global energy transition toward renewable sources has increased the urgency of integrating solar energy concepts into physics education. This study analyzes the effectiveness and characteristics of solar cell experiments in supporting scientific-based learning at the senior high school level. The research employed a quantitative pre-experimental design using a one-group pretest–posttest approach. The participants were 32 twelfth-grade students in Pontianak, Indonesia. Research instruments included a conceptual understanding test, scientific activity observation sheets, student response questionnaires, and inquiry-based experiment worksheets. Data were analyzed using mean scores, N-gain calculations, and percentage-based descriptive analysis. The results indicate a significant improvement in students’ conceptual understanding, with the average score increasing from 58 to 82 and an N-gain value of 0.57 in the moderate category. The highest improvement was observed in students’ understanding of the effect of light intensity on electrical power output. The implementation of scientific learning stages showed high percentages across all phases, particularly in the experimenting phase (94%). These findings suggest that solar cell experiments effectively enhance both conceptual understanding and science process skills. The study concludes that simple, measurable, and contextual solar cell experiments can integrate empirical measurement, data analysis, and scientific communication into a coherent learning sequence. The integration of photovoltaic experiments is recommended to strengthen energy literacy and scientific literacy in secondary physics education.